El sistema penal juvenil y los "no punibles": ¿Proteger, responsabilizar o castigar? : El quid de la cuestión = The juvenile penal system and the “non-punishable” : Protect, make responsible or punish? : The crux of the matter - Guemureman, Silvia (Oñati Socio-Legal Series, 2024)
Argentina still governs the juvenile criminal regime (decree-law 22.278/80) and is one of the few countries in the world that maintains the minimum age of criminal responsibility (MACR) at 16 years old. Precisely this circumstance has constituted around the age a problematic core of discussion with varied positions and positions on what to do with people who break the law and commit disvaluable actions and are not subject to criminal reproach. In this article I will focus on reconstructing the arc of positions for which I will use three sources: opinions of juvenile criminal justice officials and magistrates, collected through interviews; dogmatic positions, expressed in legal texts and bills with current legislative process, which regardless of the MACR set, make provisions in relation to the "non-punishable" or unimputable.